2006
DOI: 10.1111/j.1348-0421.2006.tb03786.x
|View full text |Cite
|
Sign up to set email alerts
|

A Viral Non‐Coding Region Determining Neuropathogenicity of Murine Leukemia Virus A8 Is Responsible for Envelope Protein Expression in the Rat Brain

Abstract: A neuropathogenic variant of the Friend murine leukemia virus (Fr-MLV), clone A8, induces spongiform neurodegeneration without inflammatory infiltrates when infected into neonatal rats (15). Studies with chimeras constructed from the A8 virus and the non-neuropathogenic Fr-MLV clone 57 (10) identified the env gene of A8 as a primary determinant for the induction of spongiform neurodegeneration in the brains of infected rats (15). Several MLVs induce spongiform neurodegeneration when infected into neonatal mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…Between the A8 and 57 sequences within the 0.3-kb fragment, 17 nucleotides differ (Figure 1). In our previous study, neuropathogenic R7f, which contains the A8-0.3-kb fragment and the A8- env gene on the background of 57, was shown to increase Env expression about 3-fold compared to non-neuropathogenic Rec5, which contains the 57-0.3-kb fragment and the A8- env gene on the background of 57 [5,6]. To investigate the function of the 0.3-kb fragment in viral gene expression, the full-length viral genomes of Rec5 and R7f were recombined with the luc gene, in which the viral env gene was replaced with the luc gene to produce the luciferase expression vectors Rec5-L and R7f-L, respectively (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Between the A8 and 57 sequences within the 0.3-kb fragment, 17 nucleotides differ (Figure 1). In our previous study, neuropathogenic R7f, which contains the A8-0.3-kb fragment and the A8- env gene on the background of 57, was shown to increase Env expression about 3-fold compared to non-neuropathogenic Rec5, which contains the 57-0.3-kb fragment and the A8- env gene on the background of 57 [5,6]. To investigate the function of the 0.3-kb fragment in viral gene expression, the full-length viral genomes of Rec5 and R7f were recombined with the luc gene, in which the viral env gene was replaced with the luc gene to produce the luciferase expression vectors Rec5-L and R7f-L, respectively (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…Studies with chimeras constructed from the A8 virus and the non-neuropathogenic Fr-MLV clone 57 identified a 0.3-kb KpnI-AatII fragment containing the R-U5-5’leader sequence as an important determinant of neuropathogenicity, in addition to the env gene of A8 as the primary determinant [5]. The A8-Env protein expression level is also correlated with neuropathogenicity [5,6]. Chimeric virus Rec5, which contains the A8- env gene on the background of 57, did not exhibit neuropathogenicity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also previously showed that, in addition to the env gene, a 0.3-kb fragment containing the R-U5-5 0 leader sequence of Fr-MLV A8 was necessary for neuropathogenicity (32). The 0.3-kb fragment influences the amount of Env protein in cultured cells and in rat brains (32,33). This fragment contains functional domains, such as a signal for poly(A) addition to mRNA that works in the 3 0 LTR, a PBS for reverse transcription, and a 5 0 splice site.…”
mentioning
confidence: 94%
“…Alternatively, cellular effectors, such as cytokines and inducible nitric oxide synthase, may be aberrantly expressed in the brains of infected animals (24)(25)(26)(27)(28)(29)(30)(31). In a previous study of the viral clone A8, we showed that a high level of expression of A8-Env protein in rat brain was correlated with neuropathogenicity (32)(33)(34). We also previously showed that, in addition to the env gene, a 0.3-kb fragment containing the R-U5-5 0 leader sequence of Fr-MLV A8 was necessary for neuropathogenicity (32).…”
mentioning
confidence: 98%